2017
DOI: 10.2147/ndt.s130710
|View full text |Cite
|
Sign up to set email alerts
|

Transient global amnesia: current perspectives

Abstract: Transient global amnesia (TGA) is a clinical syndrome characterized by the sudden onset of an extraordinarily large reduction of anterograde and a somewhat milder reduction of retrograde episodic long-term memory. Additionally, executive functions are described as diminished. Although it is suggested that various factors, such as migraine, focal ischemia, venous flow abnormalities, and epileptic phenomena, are involved in the pathophysiology and differential diagnosis of TGA, the factors triggering the emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
99
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 104 publications
(154 reference statements)
1
99
1
2
Order By: Relevance
“…Brain MRI All subjects underwent MRI using the following imaging protocol: sagittal-oriented 3D T2-weighted images (repetition time/ echo time = 2,500.0/244.6 ms, field of view = 256 × 256 mm 2 directions (repetition time/echo time = 8,620/85 ms, slice thickness = 2.25 mm, acquisition matrix = 120 × 120, field of view = 240 × 240 mm 2 , and bvalue = 1,000 s/mm 2 ). All of the scans were obtained using a 3.0T MRI scanner equipped with an 8-channel head coil (AchievaTx, Phillips Healthcare, Best, The Netherlands).…”
Section: Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Brain MRI All subjects underwent MRI using the following imaging protocol: sagittal-oriented 3D T2-weighted images (repetition time/ echo time = 2,500.0/244.6 ms, field of view = 256 × 256 mm 2 directions (repetition time/echo time = 8,620/85 ms, slice thickness = 2.25 mm, acquisition matrix = 120 × 120, field of view = 240 × 240 mm 2 , and bvalue = 1,000 s/mm 2 ). All of the scans were obtained using a 3.0T MRI scanner equipped with an 8-channel head coil (AchievaTx, Phillips Healthcare, Best, The Netherlands).…”
Section: Subjectsmentioning
confidence: 99%
“…Transient global amnesia (TGA) is a sudden onset of reversible anterograde amnesia with various degrees of retrograde amnesia accompanied by repetitive questioning that lasts up to 24 h [1,2]. The incidence of TGA has been estimated as 3-10 per 100,000 per year [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A sympathetic surge leading to increased epinephrine and norepinephrine serum levels may lead to vasoconstriction, transiently impeding blood flow to the hippocampus, and medial temporal lobe. 10 It is suggested that the vulnerability of neurons in the cornu ammonis field of the hippocampus to metabolic stress plays an important role in the pathophysiological cascade, leading to an impairment of hippocampal function during TGA. 11 In the presented patient, the onset of symptoms was associated with lifting of heavy weights.…”
Section: Discussionmentioning
confidence: 99%